596 A randomised phase II study of nintedanib (BIBF1120) compared to chemotherapy in patients with recurrent clear cell carcinoma of the ovary or endometrium. (NICCC/ENGOT-OV36). (14th December 2020) - Glasspool, Rosalind; Mcneish, Iain; Westermann, Anneke; Hinsley, Samantha; Ledermann, Jonathan; Ray-Coquard, Isabelle; Lawless, Claire; Ottevanger, Nelleke; Mirza, Mansoor Raza; Alexandre, Jerome
Abstract : Introduction/Background: Clear cell carcinoma (CCC) is a rare subtype of ovarian and endometrial cancer. It carries a poor prognosis and response to chemotherapy in recurrent disease is low. As angiogenesis pathways are activated in CCC, we performed a trial comparing nintedanib (BIBF1120), an orally available, triple kinase inhibitor targeting VEGFR, PDGFR and FGFR with physician's choice of chemotherapy. As the first randomised trial in relapsed CCC, it gives important information on the efficacy and toxicity of both nintedanib and chemotherapy. Here we report the ovarian cancer (OC) results. Methodology: This was an international, multi-centre, randomised, open label phase II, 3 outcome design. Patients were randomised to nintedanib 200 mg PO twice daily or chemotherapy (paclitaxel (80 mg/m2 IV Day 1, 8, 15), pegylated liposomal doxorubicin (40 mg/m2 IV) or topotecan (4 mg/m2 IV Day 1, 8, 15) every 28 days). Treatment was given until disease progression or unacceptable toxicity. The primary endpoint was progression free survival (PFS) in the ovarian cohort. Secondary objectives included overall survival (OS), response rate (RR), disease control rate (DCR) and patient reported outcomes. With 90 OC patients, the study was powered to detect an improvement in median PFS from 3 to 5 months (HR=0.6) with >90% power, 20% 1-sided significance. A statistically significant PFS difference at the 1-sided 10% level (Nintedanib superior) would give a clear signal that a phase III study is warranted. A statistically significant result at the 1-sided 20% level would require other supportive evidence. EudraCT Ref:2013-002109-73. ISRCTN No:ISRCTN50772895 . Results: 91 OC patients were included in the analysis. Median age was 54 years. Median number of previous lines was 2. After a median follow up of 20.7 months the median PFS was 2.3 months with nintedanib and 1.9 months with chemotherapy (hazard ratio=0.79, 80% CI=(0.58, 1.06), p(1-sided)=0.1521. Median OS was 9.0 and 4.9 months, respectively. Difference in OS estimates at 6 and 12 months were 19.7% and 8.9% demonstrating non-proportional hazards. RR was 2.1% and 0%, and DCR at 16 weeks was 23.4% and 9.1% (odds ratio=5.81, 80%CI=(1.79, 18.89), p(1-sided)=0.0276) with nintedanib and chemotherapy, respectively. Conclusion: The study failed to demonstrate sufficient activity of nintedanib as a monotherapy to support a phase III trial. However, the benefit in PFS, DCR and OS suggests it may be interesting to combine nintedanib with other agents in OCCC. Chemotherapy is ineffective and the outcomes for women with OCCC are extremely poor confirming the need for continued research into novel targets and therapies. Translational research is on-going (figures 1 and 2 ). Disclosures: The study was funded by an educational grant from Boehringer Ingelheim and supported by Cancer Research UK Grant ref: C8361/A15600. Author disclosures: Rosalind Glasspool: Grant funding for clinical trials from Boehringer Ingelheim, Lilly/Ignyta and Clovis. Consultancy fees, travel support and/or speaker fees for AstraZeneca, GSK/Tesaro, Clovis, Immunogen and Sotio. Site PI for studies sponsored by AstraZeneca, GSK/Tesaro, Clovis, Immunogen, Lilly and Pfizer. Samantha Hinsley: none. Jonathan Ledermann: Advisory Board and Lecture fees from AstraZeneca, Pfizer, Clovis Oncology, MSD/Merck, Eisai, Artios Pharma, GSK and grant funding from AstraZeneca and MSD/Merck. IDMC fees from Regeneron. Iain McNeish: Advisory Board fees from AstraZeneca, Clovis Oncology, Tesaro/GSK, Roche, Scancell and Carrick Therapeutics. Institutional grant funding from AstraZeneca. Jerome Alexandre: Grant funding from Janssen, MSD. Consultancy fees, travel support and/or speaker fees for AstraZeneca, GSK/Tesaro, MSD, Eisai, Novartis, Pharmamar. Site PI for studies sponsored by AstraZeneca, GSK/Tesaro, MSD, Agenus, Merck Serono, Seattle Genetics Anneke Westermann: none. Claire Lawless: none Nelleke Ottevanger: none Mansoor Raza Mirza: Personal Financial Interests: AstraZeneca, Biocad, Clovis Oncology, Geneos, Genmab, Karyopharm Therapeutics, merck, msd, Oncology Centre, Pfizer, Roche, SeatleGenetics, Sera Prognostics, Sotio, Tesaro-GSK, ZaiLab. Institutional financial interests (study grants): AstraZeneca, Boehringer Ingelheim, Clovis Oncology, Pfizer, Tesaro-GSK Isabelle Ray-Coquard: Honoraria (self) from Abbvie, Agenus, Advaxis, BMS, PharmaMar, Genmab, Pfizer, AstraZeneca, Roche, GSK, MSD, Deciphera, Mersena, Merck Sereno, Novartis, Amgen, Tesaro and Clovis; honoraria (institution) from GSK, MSD, Roche and BMS; advisory/consulting fees from Abbvie, Agenus, Advaxis, BMS, PharmaMar, Genmab, Pfizer, AstraZeneca, Roche/Genentech, GSK, MSD, Deciphera, Mersena, Merck Sereno, Novartis, Amgen, Tesaro and Clovis; research grant/funding (self) from MSD, Roche and BMS; research grant/funding (institution) from MSD, Roche, BMS, Novartis, AstraZeneca and Merck Sereno; and travel support from Roche, AstraZeneca and GSK.